Gender Equality in Employment: A View from Kazakhstan - KHAMZINA,ZHANNA (2021)
Abstract Issue under consideration: existing legal resources to support gender equality in the workplace. We systematised the provisions of Kazakhstan labour law, which should guarantee the prohibition of discrimination based on sex. The analysis resulted in five themes: “Characteristics of women’s labour”, “Analysis of labour laws differentiation”, “Evaluation of labour rights discrimination” and “Characteristics of the new labour legislation of the Republic of Kazakhstan”, “Characteristics of workers with a special social status”. We analysed the essence of the method of differentiation of labour legislation, which affects the establishment of special working conditions for women and workers with family responsibilities. We suggested a correlation between the content of legal norms and the level of guarantees of gender equality in the labour market. The results show that family circumstances, gender equality are factors influencing the formation of labour legislation, state policy in the field of wage labour. The creation of a favourable environment for labour relations of the considered categories of workers should be carried out through labour contracts, acts of the employer, social partnership agreements, collective agreements. However, priority should be given to normative acts of national action. Ensuring gender equality in fact always requires the implementation of special measures by the employer, which must be guaranteed by a coercive state mechanism. At least this thesis is true for the conditions of Kazakhstan, a country with a transition economy, when business does not have high social activity, and state power is in a period of transformation. Importance should be given to the monitoring and implementation of international obligations in the field of ensuring the prohibition of discrimination, the implementation of best practices and standards. The post-Soviet law of Kazakhstan recognises the priority of international law over national law, and this channel should be maximally used to promote the value of gender equality.